WhatsApp Messenger as a Tool to Support English Foreign Class - Muhammad Adieb Hidayatullah (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2024)
While WhatsApp Messenger has been utilized beyond its primary use as a communication tool, there is only a limited number of studies in pedagogy which highlights the importance of WhatsApp in teaching-learning activities. Therefore, this paper was initiated to present a wide perspective of valuing WhatsApp Messenger mobile app as a strategic learning tool in English Foreign Classes. This article reviews the use of WhatsApp Messenger as a tool to support English foreign language class by outlining its uses. The way WhatsApp Messenger supports English foreign language classes can be comprehended through a series of discussion which also involves teaching language skills—speaking, writing, reading, and listening. Based on the review, the articles also provide advantages and disadvantages of using WhatsApp Messenger in language classroom.